Nutraceuticals in Human Health - Durazzo, Alessandra; Lucarini, Massimo; Santini, Antonello (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nutraceuticals are a challenge for the future of prevention and therapy in healthcare. The possibility to prevent and/or support pharmacological therapy, which is nowadays mainly based on pharmaceuticals, can be a powerful tool to face pathological, chronic, long-term diseases in subjects who do not qualify for a pharmacological therapy. Nutraceuticals are obtained from vegetal or animal origin foods, and prospective research on these products will clarify their role, safety and efficacy by substantiating their role with clinical data. An effort to clarify their mechanism of action will open a door to the next generation of therapeutic agents that do not propose themselves as an alternative to drugs, but, instead, can be helpful to complement a pharmacological therapy, and to prevent the onset of chronical diseases. The market as well as the interest of people in naturally-derived remedies and less synthetic pharmaceuticals is growing, and the attention of the collective public imagination is nowadays more strongly focused on these food-derived products. This Special Issue is dedicated to the role of and perspectives on nutraceuticals in human health, examined from different angles ranging from analytical aspects to clinical trials, and from efficacy studies to beneficial effects on health conditions.